Binding of aberrant glycoproteins recognizable by Helix pomatia agglutinin in adrenal cancers. Issue 5 (27th April 2018) - Parameswaran, R.; Tan, W. B.; Nga, M. E.; Soon, G. S. T.; Ngiam, K. Y.; Brooks, S. A.; Sadler, G. P.; Mihai, R.
Abstract : Background: Aberrant glycosylation is a hallmark of cancer cells and plays an important role in oncogenesis and cancer progression including metastasis. This study aimed to assess alteration in cellular glycosylation, detected by lectin Helix pomatia agglutinin (HPA) binding, in adrenal cancers and to determine whether such altered glycosylation has prognostic significance. Methods: HPA binding lectin histochemistry was performed on archival paraffin wax‐embedded specimens of adrenocortical cancers excised from patients attending two tertiary referral centres. Benign tumours were used as controls. Demographic, histological and survival data were collected and compared between patients with HPA‐positive and HPA‐negative tumours. Results: Thirty‐two patients were treated for adrenal cancer between 2000 and 2016; their median age was 49 (range 23–79) years. Fifteen patients had functioning tumours (14 adrenal Cushing's tumours and 1 Conn's tumour). Mean(s.d.) tumour size was 127·71(49·70) mm. None of 10 control tumours expressed HPA‐binding glycoproteins. Invasion was associated with HPA‐binding glycoproteins ( P = 0·018). Local recurrence or metastatic disease did not significantly differ between HPA‐positive and HPA‐negative adrenocortical cancers. Overall survival was significantly longer in patients with HPA‐negative tumours (median survival not reached versus 22 months in patients with HPA‐positive tumours; P = 0·002). Conclusion: Altered cellular glycosylation detected by lectin HPA is associated with poor survival in patients with adrenocortical cancer. Abstract : This is the first study that shows that synthesis of O ‐linked aberrant glycoproteins, detectable by positive binding of the lectin Helix pomatia agglutinin (HPA), is a predictor of poor survival in adrenal cancer. Predictor of poor survival